Is cyclooxygenase‐1 involved in neuroinflammation?. Issue 11 (4th August 2021) - Ghazanfari, Nafiseh; van Waarde, Aren; Dierckx, Rudi A. J. O.; Doorduin, Janine; de Vries, Erik F. J.
Abstract: Purpose: Reactive microglia are an important hallmark of neuroinflammation. Reactive microglia release various inflammatory mediators, such as cytokines, chemokines, and prostaglandins, which are produced by enzymes like cyclooxygenases (COX). The inducible COX‐2 subtype has been associated with inflammation, whereas the constitutively expressed COX‐1 subtype is generally considered as a housekeeping enzyme. However, recent evidence suggests that COX‐1 can also be upregulated and may play a prominent role in the brain during neuroinflammation. In this review, we summarize the evidence that supports this involvement of COX‐1. Methods : Five databases were used to retrieve relevant studies that addressed COX‐1 in the context of neuroinflammation. The search resulted in 32 articles, describing in vitro, in vivo, post mortem, and in vivo imaging studies that specifically investigated the COX‐1 isoform under such conditions. Results : Reviewed literature generally indicated that the overexpression of COX‐1 was induced by an inflammatory stimulus, which resulted in an increased production of prostaglandin E2. The pharmacological inhibition of COX‐1 was shown to suppress the induction of inflammatory mediators like prostaglandin E2. Positron emission tomography (PET) imaging studies in animal models confirmed the overexpression of COX‐1 during neuroinflammation. The same imaging method, however, could not detect any upregulation of COX‐1 in patients with Alzheimer's disease. Conclusion : Taken together, studies in cultured cells and living rodents suggest that COX‐1 is involved in neuroinflammation. Most postmortem studies on human brains indicate that the concentration of COX‐1‐expressing microglial cells is increased near sites of inflammation. However, evidence for the involvement of COX‐1 in neuroinflammation in the living human brain is still largely lacking.